Self-Dissolving Microneedle Arrays for Transdermal Absorption Enhancement of Human Parathyroid Hormone (1-34) - Chihiro Naito; Hidemasa Katsumi; Tomoko Suzuki; Ying-shu Quan; Fumio Kamiyama; Toshiyasu Sakane; Akira Yamamoto (MDPI AG, 2018)
Human parathyroid hormone (1-34) (PTH) has been widely used as the subcutaneous injection formulation for the treatment of osteoporosis. In the present study, we developed an efficient transdermal delivery system of PTH by using dissolving microneedle arrays (MNs) composed of hyaluronic acid (HA) for the treatment of osteoporosis. PTH-loaded MNs, with needle length 800 µm, were fabricated via a micro-molding method. The stability of PTH in MNs was found to be 6-fold higher than that of PTH solution when stored at room temperature (15⁻20 °C) for one month. Micron-scale pores were clearly visible in rat skin following application of PTH-loaded MNs. PTH-loaded MNs were completely dissolved by 60 min following application to rat skin. The bioavailability (BA) of PTH relative to subcutaneous injection was 100 ± 4% following application of PTH-loaded MNs in rats. In addition, PTH-loaded MNs were found to effectively suppress decreases in bone density in a rat model of osteoporosis. Furthermore, no skin irritation was observed at the site of application in rats. These findings indicate that our dissolving MNs have a potential use in formulations for the transdermal delivery of PTH and for the treatment of osteoporosis.